Exosome-mimetics as an engineered gene-activated matrix induces in-situ vascularized osteogenesis. (July 2020) - Zha, Yao; Lin, Tianyi; Li, Yawu; Zhang, Xin; Wang, Zihao; Li, Zubing; Ye, Yongqin; Wang, Bin; Zhang, Shengmin; Wang, Jianglin
Abstract: Exosome has been considered as an instructive supplement between complicated cell therapy and single gene/protein drug treatment in the field of regenerative medicine due to its excellent biocompatibility, efficient cellular internalization and large loading capacity. Nevertheless, one major issue that extremely restricts the potential application as gene/drug vehicles is the low yield of nanoscale exosome. Moreover, the intravenous injection of targeted exosomes may cause the obstruction of blood-rich organs. Thus, herein we fabricated a specific exosome-mimetics (EMs) that could come true mass and fast production exhibited the similar size, morphology and membrane protein markers in comparison with conventional exosomes. To bypass the risk of intravenous injection and improve the efficiency of topical therapy, we simultaneously applied the engineered EMs to design a gene-activated matrix (GAM) that could be locally released by encapsulating the plasmid of vascular endothelial growth factor (VEGF) and flexibly binding onto a core-shell nanofiber film. Our findings showed that the well-designed engineered EMs-mediated GAM was able to sustainably deliver VEGF gene and significantly enhance the vascularized osteogenesis in vivo. The current work can not only consolidate the applied foundation of EMs through the breakthrough of high yield, but also provide a local and effective delivery of engineered EMs for the in-situ therapy.